Utilization of gold tailings as an additive in Portland cement - Celik, Ozlem; Elbeyli, Iffet Yakar; Piskin, Sabriye (SAGE PUBLICATIONS LTD, 2006)
Mine tailings are formed as an industrial waste during coal and ore mining and processing. In the investigated process, following the extraction of gold from the ore, the remaining tailings are subjected to a two-stage chemical treatment in order to destroy the free cyanide and to stabilize and coagulate heavy metals prior to discharge into the tailings pond. The aim of this study was the investigation of the feasibility of utilization of the tailings as an additive material in Portland cement production. For this purpose, the effects of the tailings on the compressive strength properties of the ordinary Portland cement were investigated. Chemical and physical properties, mineralogical composition, particle size distribution and microstructure of the tailings were determined by Fourier transform infrared spectroscopy (FTIR), X-ray diffractometry (XRD), particle size analyzer (Mastersizer) and scanning electron microscope (SEM). Following the characterization of the tailings, cement mortars were prepared by intergrinding Portland cement with dried tailings. Composition of the cement clinkers were adjusted to contain 5, 15, 25% (wt/wt) dried tailings and also silica fume and fly ash samples (C and F type) were added to clinker in different ratios. The mortars produced with different amounts of tailings, silica fume, fly ashes and also mixtures of them were tested for compressive strength values after 2, 7, 28 and 56 days according to the European Standard (EN 196-1). The results indicated that gold tailings up to 25% in clinker could be beneficially used as an additive in Portland cement production. It is suggested that the gold tailings used in the cement are blended with silica fume and C-type fly ash to obtain higher compressive strength values.
Keywords: tailings; gold processing; fly ash; silica fume; Portland cement; additive; wmr 871-5; FLY-ASH; STRENGTH; Engineering; Environmental Sciences & Ecology